Evaluation of the effect of jasmonic acid elicitation on composition of pigments in green callus of neem (Azadirachta indica) / Nurul Syazwani Ahmad Fauzi - Nurul Syazwani , Ahmad Fauzi (2021)
This project was carried out with the aim of determining the effects of jasmonic acid (JA) elicitation on the bioactive pigments biosynthesis and the antioxidant activities in green callus of Azadirachta indica. Plant tissue culture technique was employed to induce the formation of green callus from leaf explants of A. indica on media using 0.6 mg/L thidiazuron (CM) and three different concentrations of jasmonic acid (2, 4 and 6 mg/L) for 4 and 8 weeks of incubation time. The methanolic extracts from the green callus were used for determination of total anthocyanin content (TAC), total chlorophyll content (TCh), total carotenoid content (TC), total phenolic content (TPC), and total flavonoid content (TFC) through colorimetric and HPLC analysis. Phytochemical analysis were done using standard established phytochemical qualitative analysis. The usage of thidiazuron (TDZ) with JA did not exert any significant effect on callus fresh weight and growth index (GI). The highest amount of yield was from CM and 2 mg/L jasmonic acid (2JA) extracts for 4-week-old and 8-week-old samples respectively. Phytochemical screening revealed the presence of similar constituents in both 4-week-old and 8-week-old green callus extracts such as alkaloids, flavonoids, phenols, tannins, and terpenoids. The highest value for TAC, TCh, TC, TPC, and TFC (0.31 ± 0.00 mg/g DW, 1.00 ± 0.03 mg/g DW, 0.13 ± 0.01 mg/g DW, 3.96 ± 0.02 g GAE/g DW, and 0.55 ± 0.03 g QE/g DW respectively) of 4-week-old samples were from callus cultured on media supplemented with 6 mg/L jasmonic acid (6JA) extract. Meanwhile, the highest value for TAC, TCh, TC TPC, and TFC (0.32 ± 0.01 mg/g DW, 0.65 ± 0.00 mg/g DW, 0.10 ± 0.01 mg/g DW, 3.40 ± 0.05 g GAE/g DW, and 0.52 ± 0.01 g QE/g DW respectively) of 8-week-old samples were from callus cultured on media supplemented with 4 mg/L jasmonic acid (4JA) extract. The inhibitory concentration (IC50) value for 2, 2'-azino-bis-3-ethylbenzothiazoline-6-sulfonic acid (ABTS) of all samples were calculated and the lowest IC50 values were found to be 8.29 ± 0.10 mg/mL (6JA) for 4-week-old and 7.73 ± 0.03 mg/mL (4JA) for 8-week-old samples, respectively. The highest Ferric Reducing Antioxidant Power (FRAP) values obtained in this study were 90.60 ± 1.55 g/g (6JA), and 74.59 ± 3.91 g/g (4JA) respectively for 4- and 8-week-old samples. Overall, the findings suggest that elicitation with JA significantly improved the content of bioactive pigments in the sample, where 6 mg/L and 4 mg/L had been identified as the optimum JA concentration for 4 and 8 weeks of incubation time, respectively. Moreover, Pearson’s correlation analysis revealed a significant correlation between TAC, TCh, TC, TPC, and TFC with ABTS and FRAP assays.